Optimisation of Lactobacillus fermentation conditions and its application in the fermentation of salt-free sauerkraut - Wang, Wenlun; Li, Wenbing; Huang, Yan; Yang, Ying; Liu, Hui; Yu, Chaohang; Yuan, Qing; He, Lianmin; Hu, Qianmin; Li, Ye; Meng, Taoyan; Chen, Huanhuan; et al. (Frontiers in Microbiology, 2024)
To identify what are the dominant lactic acid bacteria (LAB) involved in the fermentation of salt-free sauerkraut, and optimize its industrial culture conditions, we isolated and identified a strain of LAB, which is referred to as Lactobacillus sp. DF_001, with the preservation number CCTCC NO: M20232593, from five different regions in Guizhou Province. Industrial culture conditions were optimized using Plackett-Burman and Central Composite design experiments, and the potential role of this LAB in salt-free sauerkraut fermentation was validated. Bioproduction was optimal with a culture time of 66 h, starch/water ratio of 1.7 % and inoculum of 0.02 %, which gave approximately three-fold higher yield than the basal culture medium DeMan-Rogosa-Sharpe medium (MRS). The LAB was used in small-scale industrial experiments. The Dafang LAB significantly enhanced the sensory score of the salt-free sauerkraut products by about 32% compared to the control group. The total acid content increased by about 32% and the sugar and nitrite contents were reduced by 67.27% and 69.58%, respectively. The total number of bacterial colonies decreased by 37.5%. All other indicators complied with the national standard, providing overall the basis to improve salt-free sauerkraut fermentation.